Remember the following rule to find the inverse of a 2x2 matrix:
![\begin{pmatrix}a&b\\c&d\end{pmatrix}^(-1)=(1)/(ad-bc)\begin{pmatrix}d&-b\\-c&a\end{pmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/k2gumjf32oo5c5d2cy086iob5jf95npl6s.png)
And it is well defined whenever ad-bc is different from 0.
The system of equations can be written as a product of a matrix A and a vector (x,y) as:
![\begin{pmatrix}4&9\\-3&-9\end{pmatrix}\begin{pmatrix}x\\y\end{pmatrix}=\begin{pmatrix}-1\\2\end{pmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/nll7t5n42j40ariqgqqt7r24e5mkuyvuul.png)
The system can be solved by multiplying both members by the inverse of the matrix (4 9 \\ -3 -9):
![\begin{gathered} \begin{pmatrix}4 & 9 \\ -3 & -9\end{pmatrix}^(-1)\begin{pmatrix}4 & 9 \\ -3 & -9\end{pmatrix}\begin{pmatrix}x \\ y\end{pmatrix}=\begin{pmatrix}4 & 9 \\ -3 & -9\end{pmatrix}^(-1)\begin{pmatrix}-1 \\ 2\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=\begin{pmatrix}4 & 9 \\ -3 & -9\end{pmatrix}^(-1)\begin{pmatrix}-1 \\ 2\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=(1)/((4)(-9)-(-3)(9))\begin{pmatrix}-9 & -9 \\ 3 & 4\end{pmatrix}\begin{pmatrix}-1 \\ 2\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=(1)/(-36+27)\begin{pmatrix}-9 & -9 \\ 3 & 4\end{pmatrix}\begin{pmatrix}-1 \\ 2\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=(1)/(-9)\begin{pmatrix}-9 & -9 \\ 3 & 4\end{pmatrix}\begin{pmatrix}-1 \\ 2\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=-(1)/(9)\begin{pmatrix}-1(-9)+2(-9) \\ -1(3)+2(4)\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=-(1)/(9)\begin{pmatrix}9-18 \\ -3+8\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=-(1)/(9)\begin{pmatrix}-9 \\ 5\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=\begin{pmatrix}-9*-(1)/(9) \\ 5*-(1)/(9)\end{pmatrix} \\ \\ \Rightarrow\begin{pmatrix}x \\ y\end{pmatrix}=\begin{pmatrix}1 \\ -(5)/(9)\end{pmatrix} \\ \\ \Rightarrow x=1,y=-(5)/(9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/whcjc0puxrsh2gddpj8juwq0v1jj1oago4.png)
Therefore, the inverse matrix used to solve the system is:
![A^(-1)=-(1)/(9)\begin{pmatrix}-9 & -9 \\ 3 & 4\end{pmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/8pu9xmkvo1kpmfxbmnduqq6t6i3ffvz3lq.png)